Strict Authentication Watermaking with Jpeg Compression (SAW-JPEG) - Jasni, Mohamad Zain (Universiti Malaysia Pahang, 2008)
This paper addresses authenticity and integrity of medical images using watermarking. Hospital Information Systems (HIS), Radiology Information Systems (RIS) and Picture Archiving and Communication Systems (PACS) now form the information infrastructure for today's healthcare as these provide new ways to store, access and distribute medical data that also involve some security ri sk. Watermarking can be seen as an additional tool for security measures. As the medical tradition is very strict with the quality of biomedical images, the watermarking method must be reversible or if not, region of Interest (ROI) needs to be defined and left intact. Watermarking should also serve as an integrity control and should be able to authenticate the medical image. Strict Authentication Watermarking with JPEG Compression (SAW-JPEG) embeds the digital signature of the image in the ROI and the image can be reverted back to its original value bit by bit if required and is able t0 survive some degree of JPEG compression. Experimental results showed that such a scheme could embed and extract the watermark at a high compression rate.